Consumer attitudes toward in-app advertising: an empirical study of Chinese young adults - Ren, Mengyao (2016)
The fast development of mobile devices has facilitated the boost of m-commerce and also mobile advertising. In-app advertising is a relatively new form of mobile advertising with great potential, but there is a lack of academic studies researching in-app advertising specifically. Hence this study investigating empirically the consumer attitudes toward in-app advertising, the factors influencing overall attitude, relationships between consumer attitude and their behaviors and the influences of gender. Chinese young adults were researched, as they are the main target audiences in world’s leading m-commerce market. The results show entertainment, interactivity and personalization were the most influential factors for overall attitude toward in-app advertising and the attitude is positively correlated with consumer behaviors. The male and female consumers also have significant differences. Credibility is the most central factor influencing the overall attitude of male consumers while the influences of personalization is not significant. However, personalization is essential for determining the attitude of female consumers. The correlation between the attitude and behaviors for male consumers is also much weaker than female consumers.